Prevalence of Hypertension in Employees of Oil and Gas Companies: A Sex-Stratified Analysis from Northwest China - Tan, Zhijun; Shang, Lei; Liu, Siming; Kyriacou, Kyriacos; Liang, Ying; Che, Tianle; Zhang, Haiyue (Cardiology and Cardiovascular Medicine, 2024)
Background: This study aims to determine whether employees of an oil and gas company in Shaanxi, China, are associated with a higher prevalence of hypertension compared to the general population's age and geographical region. Methods: Cross-sectional study is used. Participants with hypertension who fulfilled at least one of the criteria: (1) systolic blood pressure ≥140 mm Hg; (2) diastolic blood pressure ≥90 mm Hg; (3) self-reported use of antihypertensive medication in the past two weeks; or (4) self-reported history of hypertension. Result: Compared to the general population, the employees were young, with a higher proportion of men having a higher body mass index and were more likely to be alcoholics and smokers. Before propensity score matching, the prevalence of hypertension was slightly lower in the employees compared to that of the general population. After matching, overall, the employees were more likely to have hypertension compared to the general population. Gender-based subgroup analysis showed that male employees had a higher prevalence of hypertension, while the female employees had a lower prevalence of hypertension compared to the general population. Conclusion: The research results show that compared with the general population, male oilfield employees are more prone to hypertension. This finding potentially has implications for the subsequent designating of preventative modalities. Specifically, policies concerning the prevention, treatment, and control of hypertension, as well as health management in the oil and gas companies should be formulated differently for male and female workers and be more focused on males and front-line workers.